Shoaling (School of Fish) As Competitive Strategy1. (November 2015) - Muthusamy, Senthil Kumar
Abstract : As firms are witnessing uncertain business conditions and more thrust is being given to agility, speed, and market responsiveness rather than scale and size, operating in a shoaling form is a desired strategy across many industries.